Agents' Abilities. - Jaster, Romy. (Philosophical Analysis Series, 2020)
The series offers a publication forum for innovative works on all topics of analytic philosophy. The focus is on the disciplines of theoretical philosophy: metaphysics, ontology, epistemology, philosophy of language, logic. Furthermore, works that additionally include contributions to the history of philosophy are also welcome.